Chip-scale alignment of long DNA nanofibers on a patterned self-assembled monolayer. Issue 19 (18th August 2017) - Xia, J.; Su, M.
Abstract : Centimeter-long genomic DNA nanofibers produced by the interplay between surface tension and electrostatic force of micro-patterns. Abstract : Controlled alignment of long DNA nanofibers is challenging. This communication reports a method to align human genomic DNA with nearly unlimited length using lithographically produced micro-patterns of self-assembled monolayers (SAMs) with positively charged terminal groups. The micro-patterns act as local DNA reservoirs to supply DNAs for nanofiber formation, and can also stretch and align DNA nanofibers to form an ordered array by controlling the dewetting profile. By reducing the size and inter-patch distance of a micro-patch, a nearly uniform array of long DNA nanofibers can be patterned over a large area. A controlled motion of a DNA containing droplet allows for free patterning of DNA nanofibers and production of complex structures without a transfer process. Bending of DNA nanofibers due to local distortion of the contact line bridges more adjacent micro-patches and increases the chance of producing continuous nanofibers. The interplay between surface tension and electrostatic attraction of positively charged micro-patterns allows the production of long DNA nanofibers in a simple yet powerful way.